Establishment of a procedure for producing the anti-b monoclonal antibody from B4C10D9 hybridoma cell line - Trung, Nguyen Thi; Hai, Truong Nam (Academia Journal of Biology, 2017)
There are two the most important blood group system in blood transfusion, that is the ABO system and the Rh system. The anti-A or anti-B antibodies in the blood of recipient cause strongly agglutination the red blood cells of donor bearing A or B antigens on their surface respectively. So, all donated blood and received blood must be typed group for the ABO system to be safe in blood transfusion. To blood grouping, used of know antisera reacts with the whole blood samples to determine antigen on the surface of red blood cell or use of know red blood cells reacts with the individual’s serum to determine antibody. The serology method is widely used, antisera are usually monoclonal antibodies secreted by hybridoma cells. Our previous studies showed that the B4C10D9 hybridoma cell line generated anti-B monoclonal antibody was produced by hybridoma technology. This antibody causes specificity agglutination the red blood cells caring B antigen on their surface. It is classed as IgM antibody with it heavy chains are µ and κ light chains. The aim of the study was to produce the anti-B monoclonal antibody form B4C10D9 hybridoma cells line serve as a part of ABO blood grouping reagent. Based on results of experiments, procedure for producing the anti-B monoclonal antibody from B4C10D9 hybridoma cell line has also been established with following steps. At first, refresh the frozen B4C10D9 hybridoma cells and the density of B4C10D9 hybridoma cells is 4.0 x 104 cells/ml at 24 hours post-inoculation. Then the B4C10D9 hybridoma cells are splitted 1:5 every 48 hours for 2 times to obtain the cell biomass. In the next step, the hybridoma cells are splitted into 125 cm2 flasks with the initial cell density of 105 cells/ml. The B4C10D9 hybridoma cells density reach 9.9 x 106 cells/ml at 48 hours post-inoculation. After 144 hours of post-inoculation, collect culture medium and concentrate the anti-B monoclonal antibody by precipitation with saturated ammonium sulfate at a final concentration of 50%. If resuspending volume equals initial volume, then the anti-B monoclonal antibody titer reaches 1/256 and the antibody reaction intensity will be 3+. And if the obtained antibody solution volume equals one fifth of the original volume, then the anti-B monoclonal antibody titer reaches 1/1024, and the antibody reaction intensity will be 4+. Citation: Establishment of a procedure for producing the anti-b monoclonal antibody from B4C10D9 hybridoma cell line. Tap chi Sinh hoc, 39(3): 342-348. DOI: 10.15625/0866-7160/v39n3.10765. *Corresponding author: tnhai@ibt.ac.vn Received 20 August 2017, accepted 20 September 2017